The Influence of 6-Month Interdisciplinary Accompaniment on Family Caregivers' Knowledge and Self-Efficacy Regarding Diabetic Wound Care - Wantonoro Wantonoro PhD; Komarudin Komarudin PhD; Dika Rizki Imania PhD; Sigit Harun PhD; Tuan Van Nguyen PhD (SAGE Publishing, 2023)
Introduction Diabetes mellitus (DM) is a global health issue. Diabetic wounds have become a severe health complication. Interdisciplinary education and the use of homecare have led to improvements in the health of patients with chronic disease. The family caregiver's knowledge and self-efficacy positively impact the DM patient's self-care in the physical and psychological dimensions. There is still a need for interdisciplinary education to enhance family caregivers' knowledge and self-efficacy regarding diabetic wound care. Objective To determine the effect of 6 months of interdisciplinary education on family caregivers' knowledge and self-efficacy regarding diabetic wound care. Methods A quantitative longitudinal study with a quasi-experimental, one-group, pretest-posttest design was conducted. Family caregivers received 6 months of interdisciplinary education regarding diabetic wound care. The Foot Care Confidence Scale (FCCS) was used to measure the family caregivers' knowledge and self-efficacy regarding diabetic wound care. The dependent samples t test and the Wilcoxon signed-rank test were used for statistical analysis. Results Sixteen caregivers of patients with diabetic ulcer wounds in the homecare unit participated in this intervention with a 6-month follow-up. Six months of interdisciplinary education significantly increased the family caregivers' knowledge ( p =  0.001) and self-efficacy ( p =  0.001). However, there was no significant correlation between self-efficacy and gender, age, education level, or duration of wound care ( p =  0.91; 0.93; 0.38; 0.40, respectively). Long-term interdisciplinary education improved caregiver performance across genders, ages, education levels, and wound care experience durations. Conclusion Long-term interdisciplinary education of family caregivers is recommended as one method to enhance the family support system with respect to diabetic ulcer care management. In addition, interprofessional collaboration could be performed to enhance the understanding of healthcare, especially diabetic ulcer care.